Crude extract of the tropical tree Gallesia integrifolia (Phytolaccaceae) for the control of Aedes aegypti (Diptera: Culicidae) larvae - de Campos Bortolucci, Wanessa; Line Marko de Oliveira, Herika; Roque Oliva, Leiluana; Gonçalves, José Eduardo; Piau Júnior, Ranulfo; Mariano Fernandez, Carla Maria; Barros Colauto, Nelson; Linde, Giani Andrea; Cristiani Gazim, Zilda (Revista de Biología Tropical, 2021)
Introduction: Phytoinsecticides are alternatives to control insects in different stages, Gallesia integrifolia (Spreng.) Harms, Phytolacaceae family, popularly known as pau d’alho, garlic tree, and guararema in Brazil, is known due to its strong alliaceous odor because of the presence of sulfur molecules in the plant. This species presents biological activity and potential insecticide effect that is still unexploited. Objective: This study aimed to evaluate the biological activity of the ethanolic crude extract from G. integrifolia leaves, flowers, and fruits on the control of Aedes aegypti third-stage larvae and pupae. Methods: The botanical material was collected in city Umuarama, Paraná, Brazil at the coordinates (23º46’16” S & 53º19’38” WO), and altitude of 442 m, the fruits of G. integrifolia were collected in May and the leaves and flowers in December 2017. The crude extracts of G. integrifolia leaves, flowers, and fruits were prepared by dynamic maceration technique. The chemical composition of the extracts was determined by gas chromatography coupled to a mass spectrometry. The insecticidal activity of the crude extracts of G. integrifolia were carried out on larvae and pupae of A. aegypti in concentrations between 0.001 to 25 000 mg/mL, and afterwards the lethal concentrations that kill 50 % (LC50) and 99.9 % (LC99.9) were determined by probit analysis. Anticholinesterase activity was determined by bioautographic method at concentrations from 0.000095 to 50 mg/mL. Results: The yield of G. integrifolia crude extracts were 8.2, 9.1, and 17.3 % for flowers, fruits, and leaves, respectively. The chemical composition of G. integrifolia extracts was characterized by presence of fatty acid esters, phytosterols, vitamins, oxygenated diterpenes and organosulfur compounds. The flower extract presented the high amount of sulfur compounds (20.2 %) such as disulfide, bis (2-sulfhydryl ethyl) (11.9 %), 2,3,5-trithiahexane (6.2 %), 1,2,4-trithiolane (1.1 %), and 2,4-dithiapentane (1.1 %). Regarding the insecticidal activity, flower extract showed highly active with LC99.9 of 0.032 mg/mL and LC99.9 of 0.969 mg/mL on A. aegypti larvae and pupae, respectively, and the highest inhibition of acetylcholinesterase enzyme (0.00019 mg/mL) ex situ. The flower extract presented anticholinesterase and larvicide activity, respectively, 12.8 % and 35.6 % greater than the control temephos. Conclusions: This study opens new perspectives on the use of extracts from G. integrifolia as a bioinsecticide alternative for the control of A. aegypti larvae and pupae.